The effect of a change in selection procedures on students' motivation to study dentistry. (4th February 2014) - Gardner, SP; Roberts‐Thomson, KF
Abstract Background The aim of this study was to determine whether changes in student selection criteria at The University of Adelaide effected a change in motivation and influencing factors to study dentistry by comparing cohorts. Methods Online questionnaire completed by first‐year dentistry students at The University of Adelaide between 1993–1996 and 1997–2005. Results All 666 students completed the questionnaire with 647 suitable for analysis. The likelihood of students being motivated for a career in dentistry because it 'fits with family' was greater for the 1997–2005 cohort (OR = 1.68, 95% CI = 1.14–2.49, p < 0.01) than it was for 1993–1996 enrollees, whereas 'status' became less important (OR = 0.47, 95% CI = 0.30–0.73, p < 0.01). Being influenced by a dentist (OR = 2.41, 95% CI = 1.63–3.55, p < 0.001) or a dental employee (OR = 3.19, 95% CI = 0.90–4.85, p < 0.001) was much greater for the 1997–2005 group than it was for the 1993–1996 cohort. Where students came from, parents' level of education and gender were not significant in the multivariate analysis of factors associated with motivation and influences of students' career choice. Conclusions Changes to the selection procedure were associated with increased emphasis on lifestyle factors and the dental profession, but not with the desire to help people or the importance of the work itself in students' decision to study dentistry.